Developmental and reproductive costs of osmoregulation to an aquatic insect that is a key food resource to shorebirds at salt lakes threatened by rising salinity and desiccation - Herbst, David B. (Frontiers in Ecology and Evolution, 2023)
Saline lakes worldwide are undergoing drying, and as lake levels fall and areas contract, salinities increase. There is a critical need for data to guide conservation to recover the aquatic productivity that supports migratory and breeding birds that depend on these habitats. Brine flies are an important source of food to these birds and are adapted for life in saline waters owing to their capacity for osmotic regulation. The sublethal effects on growth, development and reproduction were determined in experiments and field observations with the alkali fly Cirrula hians from alkaline lakes of differing salinity. The cost of osmoregulation to fitness from rising salinity was exhibited in slower growth rates of larvae, smaller size at maturity of pupae, reduced adult emergence success, and lower fecundity. The results identify a salinity management range that would optimize life history traits and productivity of this insect as a food source for birds.